2022
DOI: 10.1186/s13063-022-06560-x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of smoking cessation into standard treatment for patients receiving opioid agonist therapy who are smoking tobacco: protocol for a randomised controlled trial (ATLAS4LAR)

Abstract: Background About 85% of patients receiving opioid agonist therapy (OAT) for opioid dependence are smoking tobacco. Although smoke-related pulmonary diseases are significant contributors to morbidity and mortality, few smoking cessation interventions are evaluated within this group, and few OAT patients are offered smoking cessation as an integrated part of their addiction treatment. This study protocol describes an integrated smoking cessation intervention aimed at patients receiving OAT and sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Prior work has suggested that tobacco use is less likely to change during pregnancy compared with other substances. 47 It is important to consider given its potential influence on low birth weight, preterm birth, and congenital anomalies 48 and that tobacco may interact with other substances to increase risk for adverse neonatal outcomes. 49 Future research may explore specific service offerings, patterns of engagement, and their impact on neonatal outcomes.…”
Section: Researchmentioning
confidence: 99%
“…Prior work has suggested that tobacco use is less likely to change during pregnancy compared with other substances. 47 It is important to consider given its potential influence on low birth weight, preterm birth, and congenital anomalies 48 and that tobacco may interact with other substances to increase risk for adverse neonatal outcomes. 49 Future research may explore specific service offerings, patterns of engagement, and their impact on neonatal outcomes.…”
Section: Researchmentioning
confidence: 99%